The interactions between gold and shariah compliant equities:the application of wavelet and multivariate GARCH analysis - Shakil, Mohammad Hassan; Mohid Rasid, Mohamed Eskandar Shah; Saiti, Buerhan (Universiti Tunku Abdul Rahman ( UTAR ), 2017)
The paper evaluates the interaction between gold and Islamic equities as a hedge and safe haven by using daily data ranging from January 1996 to September 2016 of developed and emerging market index to bestow the status of a hedge at the time of normal market condition and safe haven asset at the time of financial downturns. We applied wavelet coherence method to ascertain the best time-frequency for gold as a hedge and Multivariate GARCH analysis to find out the reaction of gold to unfavourable market conditions. The results show the interrelation between gold and equities of both developed and emerging market are inconsistent at low scales up to 64 days. Besides, after the Asian financial crisis of 1997, there was a low correlation between gold and Islamic developed and emerging market equities. It portrays that gold is hedge and safe haven for Asian financial crises for both stock market. However, after 2003 gold started to move with two markets i.e. developed and emerging and exhibited a robust positive relationship in 2005-2007 for the time-frequency between 32 to 128 days. This relationship restricted gold‘s capacity to act as a safe haven contrary to negative shocks of the global financial turmoil of 2007.